Prospects for animal traction research and development in Ethiopia - Zerbini, E.; Gebre-Wold, A. (Ethiopian Society of Animal Production, 1996)
Research on the effective utilization of animal power in small scale agriculture in Ethiopia, to sustain and enhance economic Development of the country, is essential. Draught animal power is the best alternative power source of the intermediate technology level because low wages and small farm size make it unattractive to substitute tractors for animal traction. In Ethiopia, oxen are the main draught animals, especially for tillage. Recent findings prove the possibility of using crossbred cows to replace oxen in the highlands. In other areas of the country equine and camels are also used. Comparative on-farm studies should be undertaken using improved implements and animals most suited in different areas. There is a need to identify the optimal combination of animals and drawn implements in different ecozones/farming systems in Ethiopia. Greater efficiency of the animal/implement system in relation to different environmental conditions will increase farmers productivity and income while maintaining the natural resource base. There is a need to investigate the technical and economic relationships between alternative combinations of animals, implements and soil in different environments. Multidisciplinary research should evaluate and model the physiological, mechanical and physical parameters regulating the performance of the animal/implement/soil systems. These studies will also provide economic evaluations of different systems in order to make recommendations for agricultural Development.